An Analytical Study of Thermal Instability in a Nanofluid Layer with a Vertical Magnetic Field - Bishnoi, Jaimala; Kumar, Arun (Nepal Journal of Mathematical Sciences, 2022)
The paper re-examines analytically the work of Yadav et al. ([43], [44]) (referred to as Y hereafter) wherein they have examined the combined effect of vertical magnetic field and the free-free, rigid-rigid and rigid-free boundaries on the onset of convection in an electrically conducting nanofluid layer heated from below. The key feature of the present paper is that it explains that the case M=0 ([43], [44]) is not justified either on physical or on mathematical grounds. Moreover, a number of sufficient conditions regarding the non-existence of oscillatory convection have been found.